Transformation of Theory of International Relations and Its Masters (Czech Journal of International Relations, 1999)
Iver B. Neumann, Ole Waever: The Future of International Relations. Masters in the Making. Routledge, London 1997,380 stran, ISBN 0-415-14407-8.